Teaching beliefs about teaching writting with the support of TIC - Rosa , Maria; Martinez , Edwin (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The article is associated with the doctoral research "Teachers' beliefs about the teaching of writing with ICT support in basic education in Colombia, in the Port District of Turbo". The study is developed under the qualitative approach, interpretative paradigm. It is a case study with a narrative design involving language teachers. The general objective is to explain the beliefs held by Spanish language teachers, which limit or favor the use of ICT in the teaching and learning process of writing. The categories of analysis were: 1) life history; 2) didactics used by the teacher about language; 3) use of ICT. The results show that the experiences on writing models and the use of ICTs lived during the school and professionalization stages, hinder or favor the teaching of writing. It is evident that to the extent that teachers become familiar with and appropriate technological applications, they will be able to break with traditional paradigms of education and integrate ICT in a pedagogical manner.